SOFOSBUVIR-VELPATASVIR THERAPY IN THE TREATMENT OF CHRONIC HEPATITIS C GENOTYPE 3 - Arif Qayyum Khan (Army Medical College Rawalpindi, 2021)
Objective: To determine the efficacy and safety of sofosbuvir-velpatasvir combination therapy in treatment of chronic hepatitis C genotype 3.